Excessive Daytime Sleepiness and Oral Behaviors: A Pilot Investigation Among Patients With Temporomandibular Disorders - Jie Xiang; Jiaqi Liu; Zihan Zhang; Zejin Liu; Yunhao Zheng; Yating Yi; Xueman Zhou; Jun Wang; Fan Yang; Xin Xiong (International Journal of Clinical Practice)
Conclusions: Elevated OBC scores and oral behavior level were associated with the presence of EDS in TMD patients. Behaviors including awake grinding, awake clenching, and press tongue forcibly against teeth may serve as reliable predictors of EDS in individuals with TMD. Addressing these parafunctional oral behaviors could potentially yield therapeutic benefits in the comprehensive management of TMD patients. Longitudinal trials in the future are worthwhile for a further validation.